APPRAISAL OF THE CLIMATIC RESPONSIVENESS OF THE HEALTH CENTRE BUILDING – OBAFEMI AWOLOWO UNIVERSITY, ILE-IFE - E. D., Okonta (university of eloued جامعة الوادي, 2019)
he design of a comfortable indoor climate is of great influence on occupant’s health and well-being. This study is focused on appraising the Health Centre Building of Obafemi Awolowo University`s efficiency in producing the required thermal comfort through responsiveness to the local climate or identify its deviations from this issue of climate responsiveness. The climate was analyzed using the Mahoney tables, not excluding the descriptive survey method of gathering data and the critical observation of the building envelopes. Results from the findings showed the lighting within the building needs to be improved upon, the building space should be made to be quite cool and shading devices needs to be incorporated on the required windows. Climate responsive architecture is essential because it makes the building become an intermediary on its own energy housekeeping by opening up to the energy potential of the built environment.
artical
Keywords: Climatic, Responsiveness, Architecture, Thermal Comfort, Health Centre Building